COLLABORATIVE GOVERNANCE ANALYSIS IN THE IMPLEMENTATION OF THE SMART VILLAGE PROGRAM IN BANYUWANGI REGENCY - Budi Santoso; Setyo Puguh Widodo; Mohamad Yanuarto Bramuda; Bintoro Wardiyanto (Program Studi Sosiologi Universitas Malikussaleh, 2026)
The Smart Village (Smart Kampung) Program in Banyuwangi Regency a local government innovation aimed at enhancing the quality of village-based public services through the utilization of information technology. This article seeks to analyze the implementation of the Smart Kampung Program as a collaborative governance practice involving local government, village government, communities, and non-governmental organizations within a public policy network. Employing a qualitative-descriptive approach, this study draws on literature review and analysis of policy documents relevant to the implementation of Smart Kampung in Banyuwangi Regency. The analysis is conducted using a collaborative governance framework to examine collaborative dynamics, actor capacities, and stakeholder relationships. The findings indicate that the Smart Kampung Program has established a multi-actor collaborative network and facilitated a repositioning of the local government's role as a facilitator. Nevertheless, the quality of collaboration has not yet reached a fully substantive level, as it continues to be constrained by disparities in human resource capacity, limitations in technological infrastructure, and low levels of community participation. This article underscores the importance of strengthening collaborative governance in order for Smart Kampung to sustainably generate village-based public value.